Research on the Application and Future Development of Artificial Intelligence in the Exhibition Industry - Cheng, Wenli; Li, Shaochi (Innovative Applications of AI, 2024)
With the rapid development of artificial intelligence (AI) technology, its application in the exhibition industry is becoming increasingly widespread, profoundly changing the traditional exhibition mode. This article aims to explore the current application status, advantages, challenges, and future development trends of artificial intelligence in the exhibition industry, providing reference for the digital transformation of the exhibition industry. Through case analysis, technical analysis, and trend prediction, this article reveals how artificial intelligence can improve exhibition efficiency, optimize exhibition experience, and promote industry innovation.